Розробка системи керування твердопаливним котлом - Кавун, Б. О.; Свид, І. В. (ХНУРЕ, 2018)
The developed solid fuel boiler control unit allows automation of boiler in-stallation management, reduction of enterprise expenses and the amount of labor resources.
Keywords: система управління; Arduino; система керування твердопаливним котлом